Implementation of Games Educational to Build Disciplined Character in Primary School Grade IV at SDN 2 Cikembulan - Ratnasari, Sofiana; Wakhudin, Wakhudin (UM Purwokerto Press, 2025)
Instilling disciplined personality in elementary school students is a fundamental aspect of forming a responsible personality. There is a need for an innovative approach that can integrate character education into interactive and fun learning activities through educational games. The purpose of this study was to analyze educational games in forming the disciplined character of grade IV students at SDN 2 Cikembulan. The approach used in this study was qualitative as a method of data recording through observation, interviews, and documentation methods. The subjects of the study consisted of grade IV students and teachers. This study shows that educational games play an important role in improving students' disciplined character, especially in aspects of compliance with rules, task performance, and responsibility for effective management. In addition, student participation in educational games creates a more interactive and interesting learning atmosphere and motivates students to apply discipline not only at school but also in everyday life. In addition, parents need to provide support and provide real examples when using discipline in various aspects of students' lives.